The Effect of Local Anesthetic Volume Within the Adductor Canal on Quadriceps Femoris Function Evaluated by Electromyography: A Randomized, Observer- and Subject-Blinded, Placebo-Controlled Study in Volunteers. (August 2016) - Grevstad, Ulrik; Jæger, Pia; Sørensen, Johan Kløvgaard; Gottschau, Bo; Ilfeld, Brian; Ballegaard, Martin; Hagelskjaer, Mike; Dahl, Jørgen Berg
Abstract : BACKGROUND: Single-injection adductor canal block (ACB) provides analgesia after knee surgery. Which nerves that are blocked by an ACB and what influence—if any—local anesthetic volume has on the effects remain undetermined. We hypothesized that effects on the nerve to the vastus medialis muscle (which besides being a motor nerve innervates portions of the knee) are volume-dependent. METHODS: In this assessor- and subject-blinded randomized trial, 20 volunteers were included. On 3 separate days, subjects received an ACB with different volumes (10, 20, and 30 mL) of lidocaine 1%. In addition, they received a femoral nerve block and a placebo ACB. The effect on the vastus medialis (primary endpoint) and the vastus lateralis was evaluated using noninvasive electromyography (EMG). Quadriceps femoris muscle strength was evaluated using a dynamometer. RESULTS: There was a statistically significant difference in EMG response from the vastus medialis, dependent on volume. Thirty-five percent (95% confidence interval [CI], 18–57) of the subjects had an affected vastus medialis after an ACB with 10 mL compared with 84% (95% CI, 62–94) following 20 mL ( P = 0.03) and 100% (95% CI, 84–100) when 30 mL was used ( P = 0.0001). No statistically significant differences were found between volume and effect on the vastus lateralis ( P = 0.81) or in muscle strength ( P = 0.15). CONCLUSIONS: For ACB, there is a positive correlation between local anesthetic volume and effect on the vastus medialis muscle. Despite the rather large differences in EMG recordings, there were no statistically significant differences in quadriceps femoris muscle strength. Subsequent clinical studies comparing different volumes in a surgical setting, powered to show differences not only in analgesic efficacy, but also in adverse events, are required. Abstract : Published ahead of print May 5, 2016